Menakar Filsafat Pendidikan Islam dan Filsafat Pendidikan Barat dalam Kurikulum Merdeka - Arbaiyah Yusuf‬; Moch Tolchah (Sekolah Tinggi Agama Islam YPBWI Surabaya, 2022)
This study aims to explore the comparison between Islamic and Western Philosophy of Education in the context of the Merdeka Curriculum. The research method used is library research with inductive analysis. The data used in this study consists of primary and secondary sources related to Islamic Philosophy of Education and Western Philosophy of Education, as well as official documents related to the Merdeka Curriculum in Indonesia. The results of the study show that Islamic Philosophy of Education and Western Philosophy of Education have differences in their views on educational goals and the learning methods used. Islamic Philosophy of Education emphasizes character and morality development, while Western Philosophy of Education emphasizes intellectual and creative development. In the context of the Merdeka Curriculum, the new curriculum is more influenced by Western Philosophy of Education. However, this does not mean that the Merdeka Curriculum is devoid of Islamic Philosophy of Education values. The concept, practical methods, and spirit of Islamic Philosophy of Education are integral to its values and teachings. Therefore, both philosophy of education can be integrated to achieve comprehensive and holistic educational goals. The Merdeka Curriculum emphasizes student-centered learning and the development of multiple intelligences, including intellectual, emotional, spiritual, and social intelligence. Thus, the integration of Islamic Philosophy of Education and Western Philosophy of Education in the Merdeka Curriculum can help create an inclusive and comprehensive learning environment.